Pelatihan Serunai Di Sanggar Palito Desa Pondok Kandang Kabupaten Muko - Muke Juida; Tulus Handra Kadir (SENDRATASIK UNP, 2021)
This study aims to identify and describe the training to play a traditional musical instrument called serunai at Palito Studio, Pondok Kandang Village, Mukomuko Regency. This research belongs to a descriptive study using qualitative approach. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing tools, cameras, and cellphones. The data were collected through observation, interview, and documentation. The data was analyzed through data reduction, data presentation, and data verification. The results show that the training in Palito studio uses a direct approach or "direct instruction" with the technique of introducing the song and the tone of the song to serunai as well as the way to produce the tones technically. Students immediately practice playing the songs being learned while "inserting technical in-depth material and sense of taste” when practicing to play the songs as well as applying the peer tutor method. The serunai training at the Palito studio essentially provides provisions for "basic skills" to play serunai by using material recognition method, "monitored independent training," and peer tutor method. Students who have basic abilities can deepen the technique of playing serunai and deepen their sensitivity to serunai tones in seruna performances in society ("by experience").